Inadequacy of Infrastructural Facilities in Public Universities in Nigeria: Causes, Effects and Solutions - Ayoko, Victor Olugbenga; PETER, ThankGod; Jegede, Deborah Oluwaseun (International Journal on Integrated Education, 2023)
This paper examined the factors responsible for the inadequacies of infrastructural facilities, and their effects on the quality of education in public universities in Nigeria. The paper employed qualitative and qualitative data. The paper identified poor funding, corruption, project abandonment, poor maintenance culture, poor planning, poor participation of the private sector and poor internally generated revenue as militating factors. Poor quality of teaching and learning, poor ranking, strike actions, Brain-drain and poor research activities and impacts are also identified as effects of inadequate infrastructural facilities in public universities. Based on these problems identified, the following are recommended the government should improve the funding of public universities according to the 26% minimum percentage of the total budget of a country that was recommended by UNESCO for an effective educational system The government should adopt public-private partnerships in the provision of infrastructural facilities like the school hostels and recreation centres etc.